Investigation of TPACK Skills of Elementary to Secondary School Teachers in the Context of Educational Technology: Profile and Challenges - Nur Riski Hasanah; Turmudi; Al Jupri (Postgraduate, University of Mataram, 2024)
This research addresses a gap in previous studies that typically focus on a single education level, lacking comparative analysis across primary to secondary education. The study explores the TPACK (Technological Pedagogical Content Knowledge) profiles and barriers faced by mathematics teachers at different educational levels. Previous research often lacks an in-depth examination of these barriers in mathematics teaching. The novelty lies in its multi-level comparative approach, offering insights rarely discussed in existing literature. Using mixed methods, including in-depth interviews, classroom observations, and document analysis, the study provides comprehensive data through triangulation. Findings indicate variations in TPACK skills among mathematics teachers in Banjarmasin. An elementary school teacher exhibited excellent TPACK skills despite insufficient learning documents. A junior high school teacher showed adequate skills but faced similar document preparation issues. A high school teacher displayed excellent skills with complete supporting documents. Differences in TPACK skill profiles stem from barriers such as limited technological access and infrastructure, inadequate training, high workload, teachers' attitudes toward technology, and unsupportive institutional policies. This research underscores the need for tailored interventions to address these barriers and enhance TPACK skills across educational levels.